ANALISIS KELAYAKAN FINANSIAL USAHATANI TOMAT DI DESA MANLETEN KECAMATAN TASIFETO TIMUR KABUPATEN BELU - Usboko, Maria Melania; Hendrik, Ernantje; Pudjiastuti, Sondang S.P. (Buletin Ilmiah Impas, 2024)
This research aims to determine the characteristics of tomato farming in Manleten Village, East Tasifeto District, Belu Regency, determine the income of tomato farming, and to determine the financial feasibility of tomato farming. The research method used is a survey method. The location was determined deliberately (Purposive Sampling). Samples were taken from three groups of farmers who cultivate tomatoes, totaling 55 respondents. The data used is primary data and secondary data. Data analysis uses descriptive analysis. The results of the research show that: (1) The characteristics of tomato farming in Manleten Village are carried out commercially, namely selling to traders with an average land area of 0.67 ha and total production of 16,000 kg/ha (2) The total costs incurred for tomato farming are Rp. ,82,181,450/harvested area 0.67 ha with total revenue of IDR 192,000,000/harvested area 0.67 and income of IDR 107,818,550/harvested area 0.67 ha (3) Tomato farming in Manleten Village is feasible financial to run with an R/C ratio > 1 or equal to 2.3, production BEP > 6,848 and tomato price > BEP price 5,302.